A copula-GARCH approach for analyzing dynamic conditional dependency structure between liquefied petroleum gas freight rate, product price arbitrage and crude oil price - Bai, Xiwen (2021)
Global liquefied petroleum gas (LPG) trade shows an increasing trend but is under-researched. This paper focuses on the LPG market and aims to model the dependence dynamics among LPG freight rates, crude oil price and propane location arbitrage. Conditional copula-GARCH model is applied to estimate dependencies. Different types of copulas with both time-invariant and time-varying dependence structures are fitted and their suitability has been compared. The findings suggest that firstly, Baltic LPG (BLPG) freight rate and the arbitrage between propane Far East and Middle East prices have conditional time-varying dependence and the dependence is higher in market downturns. Furthermore, BLPG and the arbitrage between Far East and US propane prices, have symmetric dependence and such a relationship has strengthened since 2013. Secondly, Middle East propane price is found to have the strongest correlation with crude oil prices compared to Far East and US propane prices, indicating higher sensitivity to crude oil price changes. Last but not least, the relationship between crude oil and BLPG is relatively weak and mostly positive.